Typification of the infrageneric names published in Kalanchoe (Crassulaceae subfam. Kalanchooideae) by Alwin Berger - Smith, Gideon F. (Phytotaxa, 2020)
As part of the treatment of the Crassulaceae for Die natürlichen Pflanzenfamilien, Berger (1930: 402–408) published 10 named and numbered (“§ 1.” to “§ 10.”), but unranked groups in the genus Kalanchoe Adanson (1763: 248) sensu stricto. Berger (1930: 404–412) recognised Kalanchoe, Bryophyllum Salisbury (1805: t. 3), and Kitchingia Baker (1881: 268) as three separate genera. However, Berger (1930) did not subdivide Bryophyllum and Kitchingia into unranked groups. Rather, he restricted his infrageneric classification, of unranked “Gruppen”, to Kalanchoe sensu stricto, i.e., K. subg. Kalanchoe sensu Smith & Figueiredo (2018).